2016
DOI: 10.1007/s00787-016-0880-z
|View full text |Cite
|
Sign up to set email alerts
|

P300 amplitude and latency in autism spectrum disorder: a meta-analysis

Abstract: Autism spectrum disorder (ASD) is an early onset neurodevelopmental disorder. Evidence suggests that ASD patients have abnormalities in information processing. Event-related potential (ERP) technique can directly record brain neural activity in real time. P300 is a positive ERP component which can measure the neuroelectrophysiological characteristics of human beings and has the potential to discover the pathological mechanism of ASD. However, P300 studies on ASD patients are incongruent and the disparities may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 74 publications
(48 reference statements)
4
44
2
2
Order By: Relevance
“…In a recent meta-analysis of ASD compared to TD, Cui et al (2016) found diverging P3 results which they attributed to high heterogeneity among the studies. They reported some evidence for reduced P3b amplitude in ASD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent meta-analysis of ASD compared to TD, Cui et al (2016) found diverging P3 results which they attributed to high heterogeneity among the studies. They reported some evidence for reduced P3b amplitude in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find significant attenuation of P3 in ASD. This discrepancy could be due to differences in participants and paradigms (Cui et al, 2016). The performance-results in our study were mainly similar between TD and ASD supporting normal abilities in classification of the stimulus and selection of responses after S2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the task state, the increased right temporal‐central alpha coherence seen in the 17 typically developing children was not seen in the 16 children with ASD . A meta‐analysis of 32 studies assessing the differences in P300 between the ASD group ( n = 407) and the typically developing control group ( n = 457) found a reduced amplitude of P300 in ASD (standardized mean difference: –0.51; 95%CI, −0.87 to 0.14) . However, it is possible that those with ASD focused on the detailed information or local features instead of the global picture, which could have added difficulty to the task demand and consequently reduced P300 amplitude .…”
Section: Neurobiology Of Asdmentioning
confidence: 99%